Diagnostic Study of Barriers for Strengthening Livelihoods of Low-Income Rural Women in Uzbekistan - Romanova, Ekaterina; Kolybashkina, Nina; Hiller, Bradley Todd; Kochkin, Evgeny (World Bank, Washington, DC, 2017)
Due to the strong economic growth maintained in the last 15 years, Uzbekistan made progress in reducing gender inequality. At the same time, several demographic and structural challenges remain; and effectively engaging women in the economy is one of them. While modernizing various sectors of the economy will foster progress and development, it may also result in setbacks for women, as they lack the skills and education needed to successfully adjust to a changing reality. While women constitute around 50 percent of the national population, their participation in the formal labor market is limited. Active women’s participation offers a reserved potential for further national economic growth and improved livelihoods for women in Uzbekistan. The link between women’s productive participation in the country’s economy and improved economic indicators is well documented across the world. Hence, to maintain strong economic growth, it is in Uzbekistan’s national interest to improve women’s participation in the formal economy. Not only can significant economic benefits be realized by mobilizing such latent productive potential, but it can be achieved in parallel with improving women’s capacity to make decisions about their own lives and act on them. The objective of this study is to examine how gender influences opportunities and risks in accessing livelihoods in Uzbekistan. It seeks to identify the constraints to, and opportunities for, increased socioeconomic resilience among rural women in Uzbekistan, and it has the potential to inform livelihoods programming. The study focuses on women in rural areas, as they represent a large portion of productive members of Uzbek society who are insufficiently integrated into the formal labor market. The study adopts a capability approach6 to understand the distinct aspirations, opportunities, and barriers for rural women in income-generating activities. It focuses on supply-side challenges faced by women and enablers of women’s work (e.g., low labor demand and lack of formal employment opportunities). The study is centered on the premise that a gender-inclusive approach should be an integral goal of livelihood support in Uzbekistan.